2019
DOI: 10.1155/2019/8562102
|View full text |Cite
|
Sign up to set email alerts
|

Computational Assessment of Thermal Conductivity of Compacted Graphite Cast Iron

Abstract: Two-dimensional FE models of CGI with different pearlite contents for thermal conductivity analysis were established according to the real metallographic images obtained by Pro/E and ANSYS. Meanwhile, thermal conductivity of CGI with different pearlite contents was tested through the laser flash method. It is indicated that the thermal conductivity of CGI declines with the increase of pearlite. When pearlite is increased from 10% to 80%, the experimental values decline from 46.63 W/m·K to 36.86 W/m·K, reducing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…The numerical simulation method can realize the control of a single microstructure variable. Previous studies, combining with experiments and 2-D or 3-D finite element analysis, reported the effects of vermicularity [ 18 ], pearlite content [ 19 ], interfacial contact thermal conductivity (ICTC) [ 20 ] and spatial connectivity [ 21 , 22 ] on the thermal conductivity of VGI, respectively. Nevertheless, finite element modeling of vermicular graphite is difficult considering graphite anisotropy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The numerical simulation method can realize the control of a single microstructure variable. Previous studies, combining with experiments and 2-D or 3-D finite element analysis, reported the effects of vermicularity [ 18 ], pearlite content [ 19 ], interfacial contact thermal conductivity (ICTC) [ 20 ] and spatial connectivity [ 21 , 22 ] on the thermal conductivity of VGI, respectively. Nevertheless, finite element modeling of vermicular graphite is difficult considering graphite anisotropy.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, if several simplified graphite models with topological equivalence [ 31 , 32 ] are established according to the 2-D and 3-D morphological characteristics of three types of graphite and the ratio of the a-axis and c-axis, it is believed that the real vermicular graphite will be included. Finally, the effect of interface between graphite and matrix is not also negligible on thermal conductivity of VGI [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The high power density (HPD) diesel engine is one of the advanced engines in the future. Compared with the traditional diesel engine, the volume and weight of HPD are reduced by more than 50%, but the rotation speed of the crankshaft and explosion pressure increase by 100% and 200%, respectively [1][2][3]. As an essential hightemperature component, the cylinder head made of compacted graphite cast iron (CGI) alloys is usually experiencing 400 °C-500 °C and 20-30 MPa explosion pressure [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative models for microstructure and thermal conductivity of vermicular graphite cast iron cylinder block based on cooling rate nonhomogeneous temperature distributions in service. Many researchers [8][9][10] have focused on the effects of microstructure including graphite morphology, graphite amount and pearlite fraction on thermal conductivity of cast iron. Matsushita et al [8] studied the influence of the nodularity on the thermal conductivity and corrected the traditional thermal conductivity model for ductile cast iron by changing the thickness of cuboid castings.…”
mentioning
confidence: 99%
“…Ma et al [9] found that when the vermicularity (40%-90%) increased, the thermal conductivity of VGI increased, according to the numerical simulation by finite element software ANSYS. Wu et al [10] found that the thermal conductivity of VGI decreased with increasing pearlite content (10%-80%) by finite element numerical simulation. These studies provide a reference for studying the quantitative effect of microstructure on thermal conductivity of VGI cylinder blocks and heads.…”
mentioning
confidence: 99%